Estudio de mercado para la creación de un local de comidas rápidas (food market) en la parroquia Siete de Octubre de la ciudad de Quevedo - Campoverde Vera, Francisco Alexander (2013)
The investigative work, it was in order to know for the acceptance of a local fast-food (Food Market) in the parish October 7 in the city of Quevedo, which implemented a study of market supply and demand in the sector, in order to establish the tastes and preferences of consumers; in the same way was a technical study that allowed to obtain suitable requirements of the company. The return on investment was determined through the study of finance, for the creation of the business. The city of Quevedo turns out to be a very competitive market, since there is a large capacity of consumption, has sites of food such as Ch Farina, KFC, King chicken, local sale of hamburgers, hot dogs. Supermarkets such as Phoenix, aunt, Super aunt, Aki, and others, those who provide and facilitate food to the consumer, all of them trying to grab prospective clients or consumers of different ages, such as children, young people and adults. In the parish seven October there is a site that provides quick meals to taste and allow the needs of consumers, despite the demand and affluence of the people, for this reason the market study was conducted to determine the level of acceptance of a local fast food (Food Market) in this sector. The creation of a local fast food in October seven parish, will generate new sources of work, will also offer quality products at affordable prices, according to the demands of the sector demand. The research was possible, because there was the participation of the inhabitants and traders in the sector was also counted with the resources needed to carry out the study of market, technical, economic and financial. To achieve the objectives and test assumptions, techniques were used types, methods, and research instruments in order to collect the information necessary to achieve the object of study and through the results of the research to determine the feasibility, feasibility and profitability of the investment project. The results achieved in the economic and financial survey reveal that create and implement Food Market in October seven parish, is required for a capital of $21.167,00, value that can be financed by the International Bank 5 year term with an interest rate of the 11.85%; cash flow showed that the investment will recover in approximately 3 years. The internal rate of return (TIR), obtained is 26.81%, which reflects the high profit margin and indicates that it is convenient to make the investment.